An Empirical Analysis of the Impact of Exchange Rate Volatility on Trade Balance in Nigeria - Esomnofu, Chiedozie I; Okpalanwabude, Ifeoma F (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The aim of this paper is to examine the effect of exchange rate volatility on trade balance in Nigeria. Data were collected from the Central Bank of Nigeria Statistical Bulletin from 1981 to 2016, and ARDL model was utilized to address the objective of this study. It was discovered from the study that exchange rate volatility has a significant negative impact on Nigerian trade balances. This negative impact could be attributable to the lack of competitiveness of locally made products in the world market. However, there is a positive relationship between exchange rate volatility and gross fixed capital formation, though this is not consistent with economic theory. This result could be linked with the overdependence of the country on foreign goods. Therefore, exchange rate volatility has a negative impact on trade balance in Nigeria. Based on these findings, whenever, the sustainable economic development is the goal of the policy makers in Nigeria, adequate strategic policy that has the capacity to stabilize the country`s exchange rate should be embarked upon by the policy makers in the country. Similarly, the Nigerian government should possess political goodwill to embark on aggressive export promotion policies that will ensure the competitiveness of domestically produced items through value added approach.